Determinants of Psychological Wellbeing in Mothers of Children with Intellectual Disability - Qasir Abbas, Rubina Feroz, Sajid Alyana (Pakistan Journal of Clinical Psychology, 2016)
Objective and Background: The purpose of current study was to investigate the significance of some familial variables in determining depression, anxiety and stress in mothers of children with intellectual disability. These variables include age of the child with intellectual disability, and the presence of other siblings, specially with reference to their gender. Hypotheses: It was hypothesized that there will be a significant difference in level of anxiety, stress and depression among mothers of children with different age groups i.e. children with ages 5 -7 years;8 - 10 years; and 11 - 13 years. It was further hypothesized that there will be a significant difference on above stated variables among mothers having only child with intellectual disability; having only female children other than intellectually disable child; and mothers having both male and female children other than child with intellectual disability. Sampling and Method: Sample of mothers (age ranges between 25 to 45 years) of children with intellectual disability, between ages 5 to 13 years was categorized according to predetermined criteria for screening on two variables, that is, 1) Age of their child with intellectual disability, 2) Number and gender of siblings of their child with intellectually disability. Depression, Anxiety and Stress Scale (DASS, Lovibond & Lovibond, 1995) was administered to find out the level of depression, anxiety and stress among mothers of children with intellectually disability. Results: Results indicate that there is a significant difference among three groups, i.e. 1) mothers having only child, 2) mothers having daughters only other than the child with intellectual disability, and 3) mothers having both male and female children other than the child with intellectual disability, on the variables of depression, anxiety and stress (F (2, 75) =18.794, p<.001; F(2, 75) =41.924, p<.001; F(2, 75) =6.603, p<.002 respectively). Results reflect the least anxiety, depression and stress in group having both male and female children other than the child with intellectual disability. Further findings reported that there is significant difference among age groups on the variables of depression and stress (F (2, 75) =4.517, p<.014; F (2, 75) =12.780, p<.001 respectively), with higher means associated with the 5 to 7 years old group of children, however, difference on variable of anxiety was found insignificant (F (2, 75) =.720, p>.05).Further implications and limitation were discussed.